1999
DOI: 10.1063/1.478251
|View full text |Cite
|
Sign up to set email alerts
|

Photodetachment photoelectron spectroscopy of doubly charged anions: S2O82−

Abstract: Articles you may be interested inStructural and electronic properties of small titanium clusters: A density functional theory and anion photoelectron spectroscopy study Study of tin-and tin cluster-cyano complexes using anion photoelectron spectroscopy and density functional calculations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…[11][12][13][14][15][16][17][18][19][20][21][22] In contrast, its anion has received significantly less attention. [23][24][25][26][27] Of immediate relevance to the current work is a previous photoelectron spectroscopic study by Dobrin et al 28 The ground state of the anion is pyramidal while the neutral is planar, leading to a very broad photoelectron spectrum with the dominant vibrational progression being the umbrella mode that connects the ground states of the neutral and the anion. The 0-0 transition was not visible because of negligible Franck-Condon overlap.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19][20][21][22] In contrast, its anion has received significantly less attention. [23][24][25][26][27] Of immediate relevance to the current work is a previous photoelectron spectroscopic study by Dobrin et al 28 The ground state of the anion is pyramidal while the neutral is planar, leading to a very broad photoelectron spectrum with the dominant vibrational progression being the umbrella mode that connects the ground states of the neutral and the anion. The 0-0 transition was not visible because of negligible Franck-Condon overlap.…”
Section: Introductionmentioning
confidence: 83%
“…The spectroscopic parameters determined in the present work are in good agreement with previous works. [25][26][27][28]57 Dobrin et al performed an in-depth analysis of their photoelectron spectrum taken at 355 nm. They found that VDE = 3.41±0.01 eV and performed a detailed Franck-Condon analysis of the vibrational progression.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of fast electrons is important for the study of multiply charged anions, for which high energy electrons often result because of the repulsive Coulomb barrier. [2][3][4][5][6][7][8][9] C. Low-temperature photoelectron spectroscopy:…”
Section: -5mentioning
confidence: 99%
“…What could be the smallest molecule with two additional electrons? The existence of these dianions was shown on several occasions, for example for fullerenes [17][18][19][20] and small molecules [21][22][23][24]. In 1999 the first observation of dianionic metal clusters was reported [25], which was followed by a systematic study of their properties [26][27][28].…”
Section: Introductionmentioning
confidence: 99%